ANALISIS PARAMETER a-VALUE DAN b-VALUE SEBAGAI MITIGASI BENCANA GEMPA BUMI DI NUSA TENGGARA TIMUR - Halimatul Aslamia; Zainul Arifin Imam Supardi (Jambura Physics Journal, 2022)
Research on seismicity parameters in the East Nusa Tenggara region can use the a-value and b-value parameters as the main earthquake precursors. The two parameters are seismic activity level and relief level. In general, both parameters use the relationship between between the frequency of earthquake occurrences and magnitude earthquake from the Guternberg-Ritcher law in the form of a graph. This study uses secondary data from the USGS earthquake details which was processed with ZMAP 6.0 software with the maximum likelihood method. Statistics of earthquakes with a magnitude of 4,5 ≤ Mw ≤ 7,9 as many as 1685 events and a depth of 675.5 km in the period 1990-2020. Based on data analysis, the Gutenberg-Ritcher equation is log N (M)=8.72-1.19M where b-value = 1.19, a-value = 8.72, a-value (annual) = 7.23, fractal dimension = 2.38. From this reason, seismic activity in the East Nusa Tenggara region is relatively high, stress levels are low and the source of the earthquake is the main faults cause structural earthquakes and even tsunamis in the seismic tectonics of the arc area basin in front of the Australian plate subducting along the subduction zone in the northern Indonesia. Therefore, the seismic parameters can be used as a long-term earthquake disaster mitigation through knowledge such as socialization before a disaster, during a disaster, and after a disaster by considering the local wisdom of the local community.